Performance of Static Power Allocation in Indoor Room on VLC-NOMA System Using Modulation PPM - Syifa Hana Afifah; Nachwan Mufti Adriansyah; Brian Pamukti (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2023)
Visible light communication (VLC) is an emerging and promising technology that exploits the visible light spectrum for data transmission. However, one of the major challenges in VLC is how to efficiently allocate the scarce modulation bandwidth to multiple users while avoiding interference and maintaining signal quality. To tackle this challenge, we propose a novel scheme that combines non-orthogonal multiple access (NOMA) with static power allocation (SPA) and pulse position modulation (PPM) in VLC. We conduct simulations in a realistic indoor scenario with a 9x9x3 m room and a single 12-watt LED at the center, using a line of sight (LOS) channel with a field of view (FOV) of 70o. The results show that our scheme achieves superior performance, with user 1 and user 2 obtaining signal-to-interference noise ratio (SINR) values of 20 dB and 74 dB, respectively. Our scheme can effectively overcome the limitations of VLC, such as low data rate, limited coverage area, and high sensitivity to ambient light noise, and pave the way for future VLC applications.